Correlation between Hypothyroidism and Incidence of Male Erectile Dysfunction in Ngargoyoso sub-distrct, Karanganyar regency - Lely Amedia Ratri; Sinu Andhi Jusup; Andri Iryawan (Nexus Kedokteran Komunitas, 2017)
Introduction: Erectile dysfunction or known as impotency is an inability to reach and to maintain erectile function. There are many factors that can cause erectile dysfunction, one of them is hypothyroidism. Hypothyroidism in male may results to erectile dysfunction because of the reduction of testoreron total rate that plays an important role in regulating sexual function in male. This study was aimed to find out the correlation between hypothyroidism and incidence of male erectile dysfunction in Ngargoyoso sub-distrct, Karanganyar regency. Methods: This study was an analytic observational study with cross sectional method. This research performed in Ngargoyoso Sub-district, Karangayar Regency with 38 samples for each hypothyroidism state. Hypothyroidism was determined by using Zulewskis clinical score and/or WHO/ICCID diagnosis criteria to found out the enlargement of thyroid gland. Erectile dysfunction was collected with International Index of Erectile Function 5 Questionnare (IIEF-5). The data was analyzed statistically using Chi-Square. Result: Percentage of male erectile dysfunction with hypothyroidism (+) was 79% and erectile dysfunction in male with hypothyroidism (-) was 45%. Chi-square analysis test of both variables showed significant correlation with p = 0.002 (p < 0.05), the strength of correlation was low, and had positive correlation (C = 0.332). Results of Odd Ratio was OR = 4,63. Conclusions: There was an association between hypothyroidism and incidence of male erectile dysfunction. Keywords: erectile dysfunction, male, hypothyroidism